Forms of Self-Harm Behavior in Adolescent Students at Boarding School - Musslifah, Anniez Rachmawati; Tjahjono, Heru Kurnianto; Khilmiyah, Akif; Suud, Fitriah M. (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2024)
Stress has an impact on uncontrolled negative emotions, which can cause individuals to engage in counterproductive behaviors such as self-harm. Self-harm is someone's act of hurting or even injuring themselves. Self-harm is a self-destructive behavior that individuals engage in to cope with emotional pain. Teenagers experience this condition more often than anyone else. Female students often encounter adolescents with similar conditions. This paper aims to determine the forms of self-harm behavior among teenage female students at boarding schools in Central Java. This study employs a qualitative research methodology with a phenomenological approach. The main subjects were three female students aged 18–21 who had engaged in self-harm behavior for at least five days or more and had been doing so for several years, as well as three supporting subjects. Data collection techniques use interviews, observation, and documentation. According to the research results, all subjects tend to self-harm when they feel pressure or have problems. Other significant research further confirms this. Adolescent female students who commit self-harm find comfort in themselves. External relationships do not provide such comfort. In research subjects, the symptoms of self-harm behavior are described as physical symptoms, psychological symptoms, and social phenomena. Meanwhile, factors that influence teenage female students to commit self-harm include genetic factors, biological factors, environmental factors, and psychological factors.